O uso de inteligência artificial no desenvolvimento de métodos de avaliação de impactos ambientais (AIA) e na elaboração de relatórios técnicos - Milani, José Leonardo Botter (2025)
This study examines the use of Artificial Intelligence (AI) in Environmental Impact Assessment (EIA), a fundamental process for identifying, predicting, and mitigating the effects of human activities on the environment. With the increasing complexity of environmental challenges and the need for more accurate and real-time assessments, AI emerges as a promising tool to transform the way EIAs are conducted. The objective of the study was to explore how AI can optimize the processes of data collection, analysis, preparation of technical reports, and public participation within the context of EIA. The methodology used includes a detailed literature review, the analysis of AI use cases in different environmental areas, and the proposal of a theoretical framework for the application of AI in EIAs. The results indicate that AI can significantly improve the accuracy and efficiency of EIA, from automating data collection to creating interactive simulations that engage the community. However, challenges such as the need for high-quality data, algorithm customization, and institutional resistance were identified as barriers to large-scale implementation. The conclusion highlights that, although AI offers opportunities to improve EIAs, a careful balance is needed between the technological benefits and the environmental impacts inherent in the use of AI itself. Thus, the gradual and strategic adoption of these technologies is recommended, with a focus on sustainability and social inclusion.